The legacy of Scott H. Decker - Pyrooz, David C. (The Oxford handbook of gangs and society, 2024)
This chapter traces the legacy of Scott H. Decker’s career in gang research. Situated in the life-course perspective, it documents the micro- and macro-level factors that shaped his legacy of scholarly impact. His entrance into the field of gang research was in response to the rise of gang violence in St. Louis in the late 1980s, along with a parallel track of professional ties to government stakeholders and community outreach. Over the course of three decades, an incredible duration of consistent and diverse scholarly and translational outputs, this chapter identifies five lasting contributions Scott has made to the study of gangs: (1) providing rich description of gangs and gang life, (2) elaborating on the group process perspective, (3) establishing disengagement from gangs as a field of inquiry, (4) advancing evidence-based policy and practice on gangs, and (5) a commitment to data derived from mixed-methods scholarship with diverse populations and research designs. What makes Scott’s contributions even more remarkable is that he did this while managing the development of two of the leading doctoral-granting criminology departments, deeply investing in the mentorship and training of colleagues and students, and maintaining an impactful research agenda outside of the field of gang research.